Smoking characteristics of Polish immigrants in Dublin - Zatonski Witold; Currie Laura M; Keogan Sheila; Clarke Vanessa; Kabir Zubair; Clancy Luke (BMC, 2008)
Abstract Background This study examined two main hypotheses: a) Polish immigrants' smoking estimates are greater than their Irish counterparts (b) Polish immigrants purchasing cigarettes from Poland smoke "heavier" (≥ 20 cigarettes a day) when compared to those purchasing cigarettes from Ireland. The study also set out to identify significant predictors of 'current' smoking (some days and everyday) among the Polish immigrants. Methods Dublin residents of Polish origin (n = 1,545) completed a previously validated Polish questionnaire in response to an advertisement in a local Polish lifestyle magazine over 5 weekends (July-August, 2007). The Office of Tobacco Control telephone-based monthly survey data were analyzed for the Irish population in Dublin for the same period (n = 484). Results Age-sex adjusted smoking estimates were: 47.6% (95% Confidence Interval [CI]: 47.3%; 48.0%) among the Poles and 27.8% (95% CI: 27.2%; 28.4%) among the general Irish population (p < 0.001). Of the57% of smokers (n = 345/606) who purchased cigarettes solely from Poland and the 33% (n = 198/606) who purchased only from Ireland, 42.6% (n = 147/345) and 41.4% (n = 82/198) were "heavy" smokers, respectively (p = 0.79). Employment (Odds Ratio [OR]: 2.89; 95% CI: 1.25-6.69), lower education (OR: 3.76; 95%CI: 2.46-5.74), and a longer stay in Ireland (>24 months) were significant predictors of current smoking among the Poles. An objective validation of the self-reported smoking history of a randomly selected sub-sample immigrant group, using expired carbon monoxide (CO) measurements, showed a highly significant correlation coefficient (r = 0.64) of expired CO levels with the reported number of cigarettes consumed (p < 0.0001). Conclusion Polish immigrants' smoking estimates are higher than their Irish counterparts, and particularly if employed, with only primary-level education, and are overseas >2 years.